Adult onset startle epilepsy. (19th October 2011) - Moseley, Brian Darryl; Shin, Cheolsu
Abstract : A 45-year-old gentleman presented for classification of spells precipitated by startle. During these spells, he would briefly lose awareness, develop tonic stiffening of his extremities and fall. He had previously been diagnosed with paroxysmal kinesogenic dyskinesia and treated unsuccessfully with clonazepam, levetiracetam and carbamazepine. The patient was admitted for prolonged video EEG monitoring, during which numerous spells induced by startle were captured. His EEG revealed brief, fast beta activity in the midline central head region during each spell consistent with startle epilepsy. The present case demonstrates that startle epilepsy can rarely be diagnosed in adults; typically seizure onset in this condition is during infancy to childhood. Our patient's ictal EEG further implicates mesial structures in the generation of startle-provoked seizures. Although our patient continued to have startle-provoked seizures at last follow-up, his improvement on lamotrigine supports observations that this anticonvulsant can reduce seizure frequency and resulting morbidity.